A Review of Strawberry Production and Price Trends from 2010 to 2022: FE1143, 4/2024 - Wade, Tara; Amon, Kelvin; Guan, Zhengfei; Elwakil, Wael (EDIS, 2024)
This publication provides information on conventional fresh strawberry acreage, volume, and pricing for California and Florida from 2010 through 2022. It is one of a series of EDIS publications that illustrate trends in Florida’s five most economically important specialty crops, excluding citrus: strawberries, bell peppers, tomatoes, watermelons, and sweet corn. The information in this publication will be useful to producers, Extension agents, and others interested in trends concerning specialty crop commodities. It serves as a single location where valuable information about the specialty crop market and production trends can be found.